Retinal photoreceptor and ganglion cell types and topographies in the red fox (Vulpes vulpes) and Arctic fox (Vulpes lagopus) - Malkemper, Erich Pascal; Peichl, Leo (Journal of comparative neurology, 2018)
The red fox (Vulpes vulpes) is the carnivore with the widest distribution in the world. Not much is known about the visual system of these predominantly forest-dwelling animals. The closely related Arctic fox (Vulpes lagopus) lives in more open tundra habitats. In search for corresponding adaptations, we examined the photoreceptors and retinal ganglion cells (RGCs), using opsin immunohistochemistry, lucifer yellow injections and Nissl staining. Both species possess a majority of middle-to-longwave-sensitive (M/L) and a minority of shortwave-sensitive (S) cones, indicating dichromatic color vision. Area centralis peak cone densities are 22,600/mm2 in the red fox and 44,800/mm2 in the Arctic fox. Both have a centro-peripheral density decrease of M/L cones, and a dorsoventrally increasing density of S cones. Rod densities and rod/cone ratios are higher in the red fox than the Arctic fox. Both species possess the carnivore-typical alpha and beta RGCs. The RGC topography shows a centro-peripheral density gradient with a distinct area centralis (mean peak density 7,900 RGCs/mm2 in the red fox and 10,000 RGCs/mm2 in the Arctic fox), a prominent visual streak of higher RGC densities in the Arctic fox, and a moderate visual streak in the red fox. Visual acuity and estimated sound localization ability were nearly identical between both species. In summary, the red fox retina shows adaptations to nocturnal activity in a forest habitat, while the Arctic fox retina is better adapted to higher light levels in the open tundra.
Keywords: Retinal Rod Photoreceptor Cells; vidění barevné; druhová specificita; zraková ostrost; životní prostředí; Eye; Foxes; Color Vision; Environment; Sound Localization; Photoreceptor Cells, Vertebrate; fotoreceptory obratlovců; imunohistochemie; lokalizace zvuku; lišky; Retinal Ganglion Cells; Species Specificity; Visual Acuity; čípky retiny; Opsins; Animals; Immunohistochemistry; oči; zvířata; opsiny; Retinal Cone Photoreceptor Cells; tyčinky retiny; retinální gangliové buňky